Efficiency bounds for estimating linear functionals of nonparametric regression models with endogenous regressors - Thomas A. Severini; Gautam Tripathi (Centre for Microdata Methods and Practice (cemmap), 2007)
The main objective of this paper is to derive the efficiency bounds for estimating certain linear functionals of an unknown structural function when the latter is not itself a conditional expectation.
Keywords: 330; Nichtparametrisches Verfahren; Regression; Instrumentalvariablen-Schätzmethode; Theorie